Stimulated emission from aluminium anode oxide films doped with rhodamine 6G. (July 2015) - Ibrayev, N.Kh.; Zeinidenov, A.K.; Aimukhanov, A.K.; Napolskii, K.S.
Abstract The spectral and luminescent properties of the rhodamine 6G dye in a porous matrix of aluminium anode oxide are studied. The films with a highly-ordered porous structure are produced using the method of two-stage anodic oxidation. By means of raster electron microscopy it is found that the diameter of the pores amounts to nearly <?CDATA 50 nm?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmgh6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and the separation between the adjacent channels is almost <?CDATA 105 nm?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmhg5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. The thickness of the films is equal to <?CDATA 55 956m?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmhch" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, and the specific surface area measured using the method of nitrogen capillary condensation is <?CDATA 15.3 m^2 g^-1?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmh4n" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Fluorescence and absorption spectra of rhodamine 6G molecules injected into the pores of the aluminium anode oxide are measured. It is found that under the excitation of samples with the surface dye concentration <?CDATA 0.3 × 10^14 molecules?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmgvq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <?CDATA m^-2?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmg9w" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> by the second harmonic of the Nd : YAG laser in the longitudinal scheme with the pumping intensity <?CDATA 0.4 MW cm^-2?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmg7s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, a narrow band of stimulated emission with the intensity maximum at the wavelength <?CDATA 572 nm?> <inline-graphic xlink:href="ark:/27927/pgj2j5zmgf3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> appears against the background of the laser-induced fluorescence spectrum. A further increase in the pumping radiation intensity leads to the narrowing of the stimulated emission band and an increase in its intensity. The obtained results demonstrate the potential possibility of using the porous films of aluminium anode oxide, doped with laser dyes, in developing active elements for quantum electronics.